From the Dwelling to the City: “Arquitectos de Cabecera”, an Alternative to Bottom-Up Planning - Olivares-Zapiain, Elisabet (Universidad de Lima. Carrera de Arquitectura, 2017)
The academic experience “Arquitectos de Cabecera”, born in the School of Architecture at Universitat Politècnica de Catalunya with one section later developed in collaboration with Medellin “Urban and Environmental Processes” [URBAM-EAFIT] Graduate school, has worked on different cases trying, it is possible to imagine the design of new city maps from a local point of view. As a complementary strategy, the local analysis, detailed case by case, provides an alternative view for professionals to recognize bit by bit the specific problems of the cities based on the problems of their citizens, which would let them create a new bottom-up cartography: from micro (housing) to macro (city). A round-trip process, where the “small part” is accepted as an adding unit of the city. The housing is a general and unknown element, a majority and constituent part of the cities.